Sequencing the ant fauna of a small island: Can metagenomic analysis enable faster identification for routine ant surveys? - Majer, Jonathan; Castalanelli, M.; Ledger, J.; Gunawardene, Nihara; Heterick, Brian (California State University Chico, 2018)
All known ant species from a small Western Australian island were subjected to DNA barcoding of the CO1 gene, with a view to using the database to identify ants by Next Generation Sequencing in subsequent, routine surveys. A further aim was to evaluate whether the data could be used to see if any new species had arrived on the island since the total fauna had been inventoried. Of the 125 unique ant species then known from the island, 72 were successfully barcoded. Those that were refractory to amplification were largely the result of sample age and/or contamination. Following this base-line barcoding, ants were sampled from 14 regular sampling sites and ant sequences were obtained from the bulked ‘metagenomic soup’. Prior to doing this, a parataxonomist had identified all ant species in the samples and returned them to the ‘soup’. Successful identification for each site varied from 38% (Sites 12 and 27) to 100% of species (Site 10). Comparison of the number of species recovered with the number of sequences obtained from each sample showed a positive correlation between the two variables. When a site had >1,000 sequences, the average recovery rate was 79%, which is in contrast to the lowest four recovery rates (Site samples 12, 22, 26 and 27), which had fewer than 440 amplicon sequences. The ability to detect individuals that occur at low frequencies is also important. We analysed each site individually to determine if a species was detected and how that related to the proportion of individuals in the pooled sample. Where a species was present at <4% of the total sample, it was only detected 10% of the time, indicating that adequate sequencing depth is critical to species recovery. We conclude that this technique was only partially successful in replacing conventional taxonomy and that it could have limited ability to detect incursions unless the new arrival is abundant. Current barcoding is no longer limited to the CO1 gene and other genes are characterised for identification of intractable groups where CO1 does not provide appropriate levels of resolution.